Nietzsche on conscious and unconscious thought - Christopher Fowles (Taylor and Francis, 2018)
While much recent attention has been directed towards Nietzsche’s reflections on the mind, and on consciousness in particular, his often-suggestive comments about thinking have thus far avoided comparable scrutiny. Starting from Nietzsche’s claims that we ‘think constantly, but [do] not know it’, and that only our conscious thinking ‘takes place in words,’ I draw out the distinct strands that underpin such remarks. The opening half of the paper focuses upon Nietzsche’s understanding of unconscious thinking, and the role of affects therein. In what remains, I consider the difference (for Nietzsche) between conscious and unconscious thought, with a particular focus on two important readings. The first, put forward by Paul Katsafanas, claims that conscious states alone have conceptually-articulated content. The second, defended most prominently by Mattia Riccardi, argues that Nietzsche’s various claims evince a form of HOT (higher-order thought) theory. I argue that neither reading is quite right, and instead propose an alternative interpretation of conscious thinking ‘in words’, which draws on work on inner speech.